ANALISIS SISTEM PENGENDALIAN INTERN ATAS PIUTANG DALAM MEMINIMALKAN RESIKO PIUTANG TAK TERTAGIH - Hermaya Ompusunggu (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
This research is about analysis of internal control system of receivables in minimizing the amount of bad debts at PT.Global Asia Seluler. The purpose of this study is to determine the application of internal control system of receivables at PT.Global Asia Seluler in determining the prospective debtor so that the amount of uncollected receivables can be minimized as small as possible and to determine the effect of the application of internal control system of receivables in minimizing the amount of bad debts with Using aging skedule on sales achieved PT.Global Asia Seluler. The results of this study will show that the implementation of internal control system of receivables PT. Global Asia Seluler has an influence in minimizing the amount of bad debts. The results are shown by the aging schedule as of December 31, 2015 on sales in 2015, where the percentage of past due due 8.69% is smaller than the company’s 10%